Cardiac Outcomes After Perinatal Sertraline Exposure in Mice. Issue 2 (August 2017) - Haskell, Sarah E.; Lo, Cecilia; Kent, Mitchell E.; Eggleston, Timothy M.; Volk, Kenneth A.; Reinking, Benjamin E.; Roghair, Robert D.
Abstract : Abstract: Selective serotonin reuptake inhibitors are prescribed to 6%–10% of pregnant women in the United States. Using an intrauterine plus neonatal exposure model to represent exposure throughout human pregnancy, we hypothesized sertraline exposure would impact intracardiac serotonin signaling and lead to small left heart syndrome in the absence of maternal psychopathology. C57BL/6 adult female mice received sertraline (5 mg·kg −1 ·d −1 IP) or saline throughout pregnancy to time of delivery. Pups maintained exposure on postnatal days 1–14 to encompass the developmental window analogous to human gestation. Sertraline-exposed mice had increased cardiac hydroxyproline content, decreased 5-HT2B receptor mRNA levels, and increased 5-HT2A receptor and serotonin transporter mRNA levels on postnatal day 21 ( P < 0.05). These changes were associated with diminished exercise capacity at 6 weeks ( P < 0.05) and decreased adult shortening fraction and stroke volume at 5 months. Isolated cardiomyocytes from neonatal sertraline-exposed mice had significantly decreased proliferation, cross-sectional area, and phosphorylation of Akt ( P < 0.05 vs. neonatal control mice). Perinatal sertraline exposure alters neonatal cardiac development and produces long-standing changes in adult cardiac function and exercise capacity. Further studies are needed to assess whether similar findings are present in the growing population that has been exposed to selective serotonin reuptake inhibitors during development.